Alloscardovia theropitheci sp. nov., isolated from the faeces of gelada baboon, the 'bleeding heart' monkey (Theropithecus gelada) - Modesto, Monica; Satti, Maria; Watanabe, Koichi; Sciavilla, Piero; Felis, Giovanna E.; Sandri, Camillo; Spiezio, Caterina; Arita, Masanori; Mattarelli, Paola (International journal of systematic and evolutionary microbiology, 2019)
A novel irregularly shaped and slightly curved rod bacterial strain, GLDI4/2 , showing activity of fructose 6-phosphate phosphoketolase was isolated from a faecal sample of an adult gelada baboon ( ). Phylogenetic analyses based on 16S rRNA genes as well as multilocus sequences (representing , and genes) and the core genome revealed that GLDI4/2 exhibited phylogenetic relatedness to DSM 21503 and to DSM 24762 . Comparative analysis of 16S rRNA gene sequences confirmed the phylogenetic results showing the highest gene sequence identity with strain DSM 21503 (96.0 %). Activities of α- and β-gluco(galacto)sidases were detected in strain GLDI4/2 , which is characteristic for almost all members of the family . Compared to other species its DNA G+C content (43.8 mol%) was very low. Phylogenetic studies and the evaluation of phenotypic characteristics, including the results of biochemical, physiological and chemotaxonomic analyses, confirmed the novel species status for strain GLDI4/2 , for which the name sp. nov. is proposed. The type strain is GLDI4/2 (=DSM 106019 =JCM 32430 ).